Issues of consent and the primary-school medical. Issue 6 (1st December 2000) - Bradley, P
Abstract : This article discusses what level of consent is needed from a child or parent before a primary-school medical can take place (ie where children are aged under 12). It also considers whether there are occasions when a doctor can see a child if the parents have failed to give consent or have explicitly refused consent. Primary-school children are considered incompetent to make decisions about their own medical treatment and so their consent does not need to be gained before a medical takes place, although it is highly desirable to obtain it. However, a doctor cannot justify a decision to see a child purely in terms of the benefit conferred on the child. Parents can be wronged if their wishes are ignored and usually those wishes should be considered overriding. Normally, general consent, which need not be fully informed, is needed before a school medical. However, if a child is considered to be in danger of being harmed significantly or suspected to have a major medical condition, a medical should go ahead regardless of the level of consent obtained from the parent, so that a reasonable standard of health is maintained for the child.